Storage stability of anthocyanins in freeze-dried elderberry pulp using low proportions of encapsulating agents - Baeza, Rosa (2020)
Fil: Baeza, Rosa. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina